Enigmatic six-headed Shiva - Temples of India Project Team (Jio Institute, 2024)
This enigmatic deity, seemingly Shaiva, has six heads and twelve hands. Although all hands are broken, one appears to hold an attribute in the form of a trident. The waist portion is buried in the earth. The headgear comprises a jata-mukuta on four of the heads on the sides, which is typically associated with Shiva, and kirita-mukuta on the front and back heads, typically associated with Vishnu. While five of the faces exhibit a fierce form, one appears benevolent. The Sadashiva form of Shiva has five faces- Ishana, Tatpurusha, Aghora, Vamadeva, and Sadyojata, represented through fierce and benevolent face types. However, labeling this image as a clear syncretic mixture of Sadashiva and Vishnu is challenging because the kirita-mukuta is placed above the fierce image types as well. The image might have some tantric associations. The Harsha Hill once had a yogini shrine. An intriguing image of Shiva/Bhairav, now housed in the Government Museum, Sikar, depicts Shiva with four hands. The upper two hands hold a skull-scepter and cobras. His lower left hand is holding a cup, or more precisely, a skull, while the fingers of his right hand dip towards its contents. The combined iconography suggests strong tantric influences. Similarly, the six-headed image under discussion may also reflect similar tantric influences.